Can all nitrogen-doped defects improve the performance of graphene anode materials for lithium-ion batteries? - Yu, Yang-Xin (Physical chemistry chemical physics : PCCP, 2013)
The electronic and adsorption properties of graphene can be changed significantly through substitutional doping with nitrogen and nitrogen decoration of vacancies. Here ab initio density functional theory with a dispersion correction was used to investigate the stability, magnetic and adsorption properties of nine defects in graphene, including both nitrogen substitutional doping and nitrogen decoration of vacancies. The results indicate that only pyridinic N2V2 defect in graphene shows a ferromagnetic spin structure with high magnetic moment and magnetic stabilization energy. Not all nitrogen-doped defects can improve the capacity of the lithium-ion batteries. The adsorption energies of a lithium atom on nitrogen-substituted graphenes are more positive, indicating that they are meta-stable and no better than the pristine graphene as anode materials of lithium-ion batteries. Nitrogen-decorated single and double vacancy defects, especially for the pyridinic N2V2 defect in graphene, can greatly improve the reversible capacity of the battery in comparison with the pristine graphene. The theoretical prediction of the reversible capacity of the battery is 1039 mA h g(-1) for the nitrogen-doped graphene material synthesized by Wu et al., which is in good agreement with the experimental data (1043 mA h g(-1)). The theoretical computations suggest that nitrogen-decorated single and double vacancy defects in graphene are the promising candidate for anode materials of lithium-ion batteries. Each nitrogen atom in the decoration can improve the reversible capacity of the battery by 63.3-124.5 mA h g(-1) in a 4 × 4 supercell of graphene. The present work provides crucial information for the development of N-doped graphene-based anode materials of lithium-ion batteries.